Portuguese cultural standards: from the Swedish perspective - Uudam, Cleelia (2009)
The objective of current master thesis is to identify Portuguese cultural standards from the Swedish perspective. The cultural standards are identified by an innovative qualitative research method called Cultural Standards Method which is based on narrative interviews. The method was chosen due to its novelty and capacity to identify the cultural differences in a subtle level. The empirical data has been gathered during interviews with Swedish people who have sufficient working experience in Portugal. The first chapter of the thesis is general introduction. The second chapter introduces the theoretical framework which is divided between introducing the essence of “culture” and giving an overview of the cross cultural studies and theories developed. Special attention is turned to the cultural dimensions compiled by Geert Hofstede. The third chapter compares Portugal and Sweden using cultural dimensions models. The forth chapter introduces the cultural standards method. The fifth chapter introduces the empirical research and presents the cultural standards obtained, comparing them with the evidence from the cultural dimensions models. Thesis ends with feedback from Swedish and with author’s epilogue that are followed by conclusion. Although based on previous cross cultural studies in management, we can describe Swedish culture as well as Portuguese culture, and in generic level predict how the encounter between representatives of both countries looks like, we are not able to determine in more subtle level what are the differences emerging during such encounter. The Cultural Standards Method enables us to see what specific features a Swedish person has to be prepared to face in an encounter with the Portuguese culture.